A novel immune function biomarker identifies patients at risk of clinical events early following liver transplantation. Issue 4 (April 2017) - Sood, Siddharth; Haifer, Craig; Yu, Lijia; Pavlovic, Julie; Churilov, Leonid; Gow, Paul J.; Jones, Robert M.; Angus, Peter W.; Visvanathan, Kumar; Testro, Adam G.
Abstract : Balancing immunosuppression after liver transplant is difficult, with clinical events common. We investigate whether a novel immune biomarker based on a laboratory platform with widespread availability that measures interferon γ (IFNγ) after stimulation with a lyophilized ball containing an adaptive and innate immune stimulant can predict events following transplantation. A total of 75 adult transplant recipients were prospectively monitored in a blinded, observational study; 55/75 (73.3%) patients experienced a total of 89 clinical events. Most events occurred within the first month. Low week 1 results were significantly associated with risk of early infection (area under the receiver operating characteristic curve [AUROC], 0.74; P = 0.008). IFNγ ≤ 1.30 IU/mL (likelihood ratio positive, 1.93; sensitivity, 71.4%; specificity, 63.0%) was associated with the highest risk for infection with minimal rejection risk. Nearly half the cohort (27/60, 45.0%) expressed IFNγ ≤ 1.30 IU/mL. Moreover, an elevated week 1 result was significantly associated with the risk of rejection within the first month after transplant (AUROC, 0.77; P = 0.002), but no episodes of infection. On multivariate logistic regression, IFNγ ≥ 4.49 IU/mL (odds ratio, 4.75) may be an independent predictor of rejection ( P = 0.05). In conclusion, low IFNγ suggesting oversuppression is associated with infections, whereas high IFNγ indicating undersuppression is associated with rejection. This assay offers the potential to allow individualization and optimization of immunosuppression that could fundamentally alter the way patients are managed following transplantation. Liver Transplantation 23 487–497 2017 AASLD.